Nowcasting BRIC+M in Real Time - Tatjana Dahlhaus; Justin-Damien Guénette; Garima Vasishtha (Bank of Canada, 2015)
Emerging-market economies have become increasingly important in driving global GDP growth over the past 10 to 15 years. This has made timely and accurate assessment of current and future economic activity in emerging markets important for policy-makers not only in these countries but also in advanced economies. This paper uses state-of-theart dynamic factor models (DFMs) to nowcast real GDP growth in five major emerging markets - Brazil, Russia, India, China and Mexico ("BRIC+M"). The DFM framework allows us to efficiently handle data series characterized by different publication lags, frequencies and sample lengths. This framework is particularly suitable for emerging markets for which many indicators are subject to significant publication lags and/or have been compiled only recently. The methodology also allows us to extract model-based "news" from a data release and assess the impact of this news on nowcast revisions. Results show that the DFMs generally outperform simple univariate benchmark models for the BRIC+M. Overall, our results suggest that the DFM framework provides reliable nowcasts for GDP growth for the emerging markets under consideration.
Keywords: C33; C53; E37; 330; Econometric and statistical methods; International topics